PATIENT EXPERIENCE OF INPATIENTS AT CANCER CENTER, DANANG C HOSPITAL IN 2025 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the experience of inpatients and analyze some factors affecting the experience of inpatients at Cancer Center, Danang C Hospital in 2025.Methods: The study used a combination of quantitative and qualitative research methods. The study period was from December 2024 to September 2025.Results: The average inpatient treatment experience score at the hospital was 9.03/10, with 88.7% of patients reporting a positive experience. Factors affecting the experience included education level, number of treatments, understanding of disease stage, and waiting time for inpatient admission. Patients with health insurance, stable finances, and multiple previous treatments often had better experiences, while older age, underlying medical conditions, and financial burden reduced satisfaction levels.Conclusion: The inpatient experience at Cancer Center, Danang C Hospital in 2025 was generally positive, especially regarding service attitude, clarity in counseling, and discharge procedures. However, it is necessary to strengthen financial support for disadvantaged patients, reduce waiting times, improve the timeliness of medical examination and treatment, and promote communication and counseling to help patients better understand their disease stage and adhere to treatment.
Keywords: Experience, inpatient, patient, cancer.